The Double Flip: Applying a Flipped Learning Approach to Teach the Teacher and Improve Student Satisfaction - Kehoe, Thomas; Schofield, Penelope; Branigan, Elizabeth; Wilmore, Michael (Journal of University Teaching and Learning Practice, 2018)
This paper describes a professional development (PD) program for academics at an Australian university designed to model good blended curriculum design and effective use of contemporary learning technologies. It evaluates a case study from the pilot of this program involving a postgraduate psychology course to illustrate one of the most challenging examples and in turn the potential impact of the approach developed. Academic developers face known barriers, including time constraints, interdisciplinary miscommunication, and change resistance, when introducing academics to new approaches to learning and teaching. This PD sought to promote change by modelling a shift from “sage on the stage” to “guide on the side,” through use of flipped and blended learning approaches by the academic developer. The case study found the teacher gained confidence in these methods and student satisfaction ratings increased.